Health Literacy: Intervention and Outcome in Child Healthcare in Bangladesh - Sharmin, Saida; Nurunnabi, Abu Sadat Mohammad; Ashique, Shamsi Sumaiya; Jahan, Asmay; Begum, Munira (Community Based Medical Journal, 2023)
Bangladesh made significant improvements in child healthcare and achieved its Millennium Development Goal (MDG) 4 (to reduce child mortality). In 2010, the United Nations recognized Bangladesh for its exceptional progress towards MDG 4 to reduce child and maternal mortality in the face of many socioeconomic challenges. We are also committed to achieve our Sustainable Development Goal (SDG) by 2030. Health education department of Government of Bangladesh prioritized several essential health interventions over the past decades. There were focuses on expanding immunization, tackling diarrhoea and pneumonia, vitamin A campaign, prevention of blindness, iodine deficiency, and improving adolescent health. These programmes and strategies were scaled-up nationwide. The government along with its stakeholders promoted widespread availability and affordability of those health literacy interventions with an emphasis on community-based approaches. As a result, inequities in coverage of specific interventions declined; this may explain the improvements seen amongst even the most disadvantaged populations of the country. Media campaigns played a great role, which were undertaken in Bangladesh for decades and involved a nationally broadcast television supported by radio, television, newspaper, and billboard advertisements and local promotion activities. We expect that ongoing public private partnerships (PPPs) in which the government contracts NGOs and the private sector will enable us greater success and coverage of health information and literacy services throughout the country. CBMJ 2023 January: Vol. 12 No. 01 P: 124-128